Structure and nonlinear optical properties of novel transparent glass-ceramics based on Co2+:ZnO nanocrystals. (8th April 2016) - Loiko, P A; Dymshits, O S; Vitkin, V V; Skoptsov, N A; Zhilin, A A; Shemchuk, D V; Ya Tsenter, M; Bogdanov, K V; Malyarevich, A M; Glazunov, I V; Mateos, X; Yumashev, K V
Abstract: Transparent glass-ceramics (GCs) based on Co 2+ :ZnO nanocrystals (mean diameter, 11 nm) are synthesized on the basis of cobalt-doped glasses of the K2 O–ZnO–Al2 O3 –SiO2 system. For these GCs, the absorption band related to the 4 A2 ( 4 F) → 4 T1 ( 4 F) transition of Co 2+ ions in tetrahedral sites spans until 1.73 μ m. Saturation of the absorption is demonstrated at 1.54 μ m, with a saturation fluence F s = 0.8 ± 0.1 Jcm −2 ( σ GSA = 1.7 ± 0.2 × 10 −19 cm 2 ) and a recovery time of 890 ± 10 ns. Passive Q-switching of an Er, Yb:glass laser is realized with the synthesized GCs. This laser generated 0.37 mJ/100 ns pulses at 1.54 μ m. The developed GCs are promising as saturable absorbers for 1.6–1.7 μ m crystalline erbium lasers.